Climate Changes Projection for Land and Forest Fire Risk Assessment in West Kalimantan - Jadmiko, S.D.; Murdiyarso, Daniel; Faqih, A. (IOP Publishing, 2017)
Risk analysis is a method used to determine the probability of disaster in the current and future. This research analyse of fire risk in West Kalimantan by using extreme climate and vulnerability analysis. Extreme climate was calculated based on the extreme dry rainfall from regional climate model RegCM4.4 outputs. Vulnerability analysis was conducted by using a composite mapping analysis used hotspot data and eleven indicators of vulnerability. We found that very high level of extreme dry rainfall located in the southern region and the western coast area of West Kalimantan. This condition was influenced by environment factors such as topography and land use. Extreme dry rainfall also associated with the pattern of annual rainfall in West Kalimantan which ranges between 1753-4861 mm. Modelling of the vulnerability of land and forest fires in West Kalimantan showed that the land use has impact 24% on the vulnerability model. The results of the vulnerability model analysis shows that the plantations areas and secondary swamp forests are highly vulnerable, particularly on the peat area with depth about 50-200 cm. The analysis of land and forest fires risk found that the vulnerable areas have high risk which is largely unmanaged plantation areas and peatlands.